2022
DOI: 10.3389/fnhum.2022.949395
|View full text |Cite
|
Sign up to set email alerts
|

Visual cortical γ−aminobutyric acid and perceptual suppression in amblyopia

Abstract: In amblyopia, abnormal visual experience during development leads to an enduring loss of visual acuity in adulthood. Physiological studies in animal models suggest that intracortical GABAergic inhibition may mediate visual deficits in amblyopia. To better understand the relationship between visual cortical γ-aminobutyric acid (GABA) and perceptual suppression in persons with amblyopia (PWA), we employed magnetic resonance spectroscopy (MRS) to quantify GABA levels in both PWA and normally-sighted persons (NSP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Restoring cortical synaptic inhibition may be relevant to a range of developmental disorders. For example, GABA levels in visual cortex are reduced in amblyopia and this is correlated with weaker perceptual suppression by the amblyopic eye (Mukerji et al, 2022). By directly comparing the impact of restoring Gabra1 and Gabbr1b protein expression we have shown that this effect was only achieved by upregulating GABA B receptor-mediated inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Restoring cortical synaptic inhibition may be relevant to a range of developmental disorders. For example, GABA levels in visual cortex are reduced in amblyopia and this is correlated with weaker perceptual suppression by the amblyopic eye (Mukerji et al, 2022). By directly comparing the impact of restoring Gabra1 and Gabbr1b protein expression we have shown that this effect was only achieved by upregulating GABA B receptor-mediated inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of VEPs observed after MI may also involve an alteration of inhibition that could relieve an imbalance in interocular perceptual suppression thought to contribute to the deficits in vision linked to amblyopia ( Harrad and Hess, 1992 ; Sengpiel et al, 2006 ; Li et al, 2011 ; Hess and Thompson, 2015 ; Mukerji et al, 2022 ). The shift in interocular suppression may originate from a modification of the number or size of inhibitory synapses that follow a period of MD ( Chen et al, 2011 ; van Versendaal et al, 2012 ), and which, along with a reduction in inhibitory drive ( Kuhlman et al, 2013 ), may produce a weakening of inhibitory synapses serving the deprived eye.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in center-surround contrast suppression have been associated with altered neurotransmitter levels in human visual cortex, notably the major inhibitory neurotransmitter GABA. 31 , 63 , 64 There is also evidence that other mechanisms play a role in determining center-surround suppressive effects, such as withdrawal of excitation not primarily driven by GABA-mediated inhibition 27 or cholinergic system involvement. 28 , 29 There is some evidence of discrete changes in components of excitatory (glutamate) and inhibitory (GABA) neurotransmitter systems that could impact on the circulating neurotransmitter levels—for example, receptor expression levels, synthesis, vesicular transport, and release of neurotransmitter.…”
Section: Discussionmentioning
confidence: 99%